2023
DOI: 10.3389/fendo.2023.1116770
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of placental endocrine function and fetal brain development in a mouse model of small for gestational age

Abstract: Conditions such as small for gestational age (SGA), which is defined as birthweight less than 10th percentile for gestational age can predispose to neurodevelopmental abnormalities compared to babies with normal birthweight. Fetal growth and birthweight depend on placental function, as this organ transports substrates to the developing fetus and it acts as a source of endocrine factors, including steroids and prolactins that are required for fetal development and pregnancy maintenance. To advance our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Fetal brain RNA was extracted with RNeasy plus Mini Kits (Qiagen) as previously described (Lopez-Tello and Sferruzzi-Perri, 2023). Reverse transcription was performed using the cDNA reverse transcription kit (Applied Biosystems) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal brain RNA was extracted with RNeasy plus Mini Kits (Qiagen) as previously described (Lopez-Tello and Sferruzzi-Perri, 2023). Reverse transcription was performed using the cDNA reverse transcription kit (Applied Biosystems) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Brain protein extraction and Western blotting were performed as previously described (Lopez-Tello and Sferruzzi-Perri, 2023). Briefly, brain samples were lysed with radioimmunoprecipitation assay (RIPA) lysis buffer (R0278-50M, Sigma Aldrich) supplemented with protease inhibitor cocktail mix (11836170001, Roche), 1mM β-glycerophosphate (G-9891, Sigma Aldrich) and 1mM sodium orthovanadate (S65089891, Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments have shown that the dysregulation of hormones secreted by the placenta during pregnancy may alter insulin signaling and adversely affect fetal growth[ 11 , 48 ]. A number of studies have shown that the level of human placental lactogen (HPL) in GDM patients increases during the third trimester of pregnancy, and the expression levels of HPL in mothers and umbilical cord blood are closely related to placental weight and birth weight[ 49 , 50 ].…”
Section: Effects On the Hormone Secretion Function Of The Placentamentioning
confidence: 99%
“…Previous studies have shown that metabolic abnormalities in GDM patients could damage the structure, morphology and functions of the placenta and lead to pathological changes, affecting the energy conversion between the mother and the fetus, and affecting fetal development[ 8 ]. In recent years, an increasing number of studies have shown that the placenta is associated with diseases such as obesity in offspring[ 9 ], cardiovascular diseases[ 10 ] and impaired neurodevelopment[ 11 ], implying the importance of the placenta during fetal development.…”
Section: Introductionmentioning
confidence: 99%